Foreign experience of natural resources management on the example of the development Norway economy - Magda, R.; Shugaipova, Zh. (BUKETOV BUSINESS REVIEW, 2018)
This article discusses the need to use foreign experience in the oil and gas complex of Kazakhstan. Significant hydrocarbon reserves, favorable geographical position of our country, further increase in oil and gas production indicate that in the future the oil and gas complex will occupy a leading position in the economy of the Republic of Kazakhstan. With its development, there are certain hopes for the further socio-economic development of the country. Cash receipts from oil and gas companies make up the bulk of the state budget. The oil and gas complex has a decisive impact on the social and economic development of our country and its individual regions, in fact,it is a donor for the entire economy of the state, contributes to the development of other sectors of the economy. The implementation of the most important social programs in the regions and the entire state is connected with the work of oil and gas companies. Kazakhstan’s study of the experience of such a country as Norway, which has a highly developed economy and has managed to make its oil reserves an economic miracle, will help our country to maximize national economic interests. The formulation of these interests and their consolidation in the highest legislative documents of the country should become a starting point in reforming the system of state regulation by the domestic oil and gas complex.